Visualization of Similar Patients in a Clinical Decision Support System for Rare Diseases - A Focus Group Study - Sedlmayr, Martin; Schaaf, Jannik; Sedlmayr, Martin; Prokosch, Hans-Ulrich; Tegtbauer, Niels; Kadioglu, Dennis; Schaefer, Johanna; Boeker, Martin; Storf, Holger (German Medical Data Sciences: Bringing Data to Life, 2021)
The diagnosis of patients with rare diseases is often delayed. A Clinical Decision Support System using similarity analysis of patient-based data may have the potential to support the diagnosis of patients with rare diseases. This qualitative study has the objective to investigate how the result of a patient similarity analysis should be presented to a physician to enable diagnosis support. We conducted a focus group with physicians practicing in rare diseases as well as medical informatics researchers. To prepare the focus group, a literature search was performed to check the current state of research regarding visualization of similar patients. We then created software-mockups for the presentation of these visualization methods for the discussion within the focus group. Two persons took independently field notes for data collection of the focus group. A questionnaire was distributed to the participants to rate the visualization methods. The results show that four visualization methods are promising for the visualization of similar patients: "Patient on demand table", "Criteria selection", "Time-Series chart" and "Patient timeline. "Patient on demand table" shows a direct comparison of patient characteristics, whereas "Criteria selection" allows the selection of different patient criteria to get deeper insights into the data. The "Time-Series chart" shows the time course of clinical parameters (e.g. blood pressure) whereas a "Patient timeline" indicates which time events exist for a patient (e.g. several symptoms on different dates). In the future, we will develop a software-prototype of the Clinical Decision Support System to include the visualization methods and evaluate the clinical usage.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Clinical Decision Support; Rare Diseases; Requirements analysis